1992
DOI: 10.1002/mcs.1220040208
|View full text |Cite
|
Sign up to set email alerts
|

Molecular formula determination of halogenated compounds in environmental samples using gas chromatography and atomic emission dection

Abstract: Abstract. Atomic emission spectroscopy coupled with capillary gas chromatography (GC) has been evaluated for molecular formula determination of several chlorinated and brominated compounds present in three environmental samples. Variations in elemental responses due to compound type, poor chromatographic resolution, and small signals relative to the background were all found to complicate molecular formula calculations. About 20% of the calculated molecular formulas presented in this paper agreed with theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…No fluorinated compounds were detected. Previous work with this extract have been performed with GC-AED and GC-MS [14,15]. These have shown that peaks number 1 and 2 were trichloro-trimethylbenzenes and peak number 3 was a bromo-dichloro-methylbenzene.…”
Section: Applicationsmentioning
confidence: 99%
“…No fluorinated compounds were detected. Previous work with this extract have been performed with GC-AED and GC-MS [14,15]. These have shown that peaks number 1 and 2 were trichloro-trimethylbenzenes and peak number 3 was a bromo-dichloro-methylbenzene.…”
Section: Applicationsmentioning
confidence: 99%
“…For GC-AED, previous studies have demonstrated that response in the bromine-selective mode is dependent only on the amount of bromine introduced into the plasma [8,9,11,12,[18][19][20][21]. Thus, bromine-responses are almost independent of molecular structures and this has been demonstrated for a broad range of different compounds including brominated alkylbenzenes [15,16]. Based on this, quantification of the brominated alkylbenzenes identified above was accomplished rapidly with a single calibration curve for bromine (Table I).…”
Section: Response Factors Quantification and Detection Limitsmentioning
confidence: 99%
“…Thus, although the knowledge obtained by GC-AED was limited to elemental information, this effectively complemented the results from GC-EIMS. In addition to the qualitative elemental information, GC-AED may be utilized for the estimation of molecular formulas [15,16].In the present work however, this was of relatively little interest because most of the brominated alkylbenzenes coeluted with chlorinated matrix constituents. Thus, poor accuracy was expected for the molecular formulas estimated by GC-AED.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The identication of organic compounds by atomic emission spectrometry (AES) through determination of their empirical formula has so far only been carried out by gas chromatography coupled to a microwave induced plasma (MIP). [10][11][12][13][14][15][16][17][18] However, this approach has a number of drawbacks. It is only applicable to relatively volatile thermally-stable compounds, thereby requiring derivatisation of non-volatile analytes, which signicantly increases the analysis time and sources of error.…”
Section: Introductionmentioning
confidence: 99%